EFFECT OF CO-CULTURE OF ORIGANUM VULGARE AND THYMUS VULGARIS ON ESSENTIAL OIL PRODUCTION - Asghari, G.; Ardakani, M. S; Hossein, A.; Shakibai, J. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Origanum vulgare and Thymus vulgaris are plants containing essential oils. In this study the effect of co-culturing O. vulgare and T. vulgaris on essential oil production was investigated. O. vulgare and T. vulgaris seeds’ surfaces were sterilized, and were transferred to the Petri dishes to produce seedlings. Callus culture was established from the seedlings and a cell suspension culture was obtained from the callus. The cultures were established in MS media supplemented with sucrose. A Co-culture of two plants was established. Dichloromethane extract of the cultured cells was prepared and subjected to GC analysis. Only Thymol was produced in cultured cells of O. vulgare and T. vulgaris as well as in their co-culture. It seems that enzymes involved in biosynthetic pathways of the volatile oils in these plants are not able to influence the terpen-biosynthesis of another plant.